Using the New "Life's Essential 8" Metrics to Evaluate Trends in Cardiovascular Health Among US Adults From 2005 to 2018: Analysis of Serial Cross-sectional Studies - Cheng Li; Yanzhi Li; Min Zhao; Cheng Zhang; Pascal Bovet; Bo Xi (JMIR Publications, 2023)
BackgroundThe recently published "Life's Essential 8" (LE8) by the American Heart Association has overcome some limitations in evaluating cardiovascular health (CVH) in the previous "Life's Simple 7." ObjectiveWe aimed to examine the secular trends in CVH, as assessed by the LE8, in US adults from 2005 to 2018. MethodsUsing cross-sectional data from the National Health and Nutrition Examination Survey between 2005-2006 and 2017-2018, we calculated the age-standardized mean scores of overall CVH and each of the LE8 components, where a higher score (range 0-100 points) means a better health status. A total of 21,667 adults aged 20-79 years were included in this analysis. ResultsThe overall CVH did not significantly change between 2005-2006 and 2017-2018 (65.5, 95% CI 63.9-67.1 to 65.0, 95% CI 62.8-67.1; P=.82). The individual metrics did not significantly change for diet (41.0, 95% CI 38.0-43.9 to 41.5, 95% CI 36.5-46.6; P=.94), physical activity (57.5, 95% CI 53.0-61.9 to 53.0, 95% CI 48.7-57.3; P=.26), and blood pressure (68.4, 95% CI 65.2-71.5 to 68.6, 95% CI 65.3-71.9, P=.35), improved for nicotine exposure (64.7, 95% CI 61.1-68.4 to 71.9, 95% CI 67.7-76.2; P<.001), sleep health (83.7, 95% CI 81.6-85.7 to 84.1, 95% CI 81.2-87.1; P=.006), and blood lipids (61.6, 95% CI 59.1-64.0 to 67.0, 95% CI 63.5-70.4; P<.001), and worsened for BMI (63.4, 95% CI 59.7-67.1 to 56.2, 95% CI 52.5-59.9; P<.001) and blood glucose (83.9, 95% CI 82.4-85.4 to 77.4, 95% CI 74.5-80.3; P<.001). ConclusionsAccording to the LE8, the overall CVH did not change among US adults from 2005 to 2018, as well as 3 components (diet, physical activity, and blood pressure). Other metrics such as nicotine exposure, blood lipids, and sleep health improved, while BMI and blood glucose deteriorated over time.